A Cooperative Empowerment Model for Micro, Small and Medium Enterprises (MSMEs) - Suratman, Maman; Febrianti, Adjeng Mariana; Hermina, Nurul (Universitas Pasundan, 2024)
This research is motivated by the idea that micro, small, and medium cooperative enterprises (MSME cooperatives) have a strategic role to play in the national economic system that seeks to create an advanced, fair, and prosperous society based on Pancasila—Indonesia’s foundational philosophical principles—as well as the nation’s 1945 constitution. It is apparent that, in reality, this empowerment has not been effective so a model needs to be established. This research used an explanatory survey method using descriptive and verification analysis techniques. The population of the survey comprised tofu and tempeh producers (MSMEs) located in the Kopti production center in the city of Bandung in West Java. Then, 32 of these MSMEs were selected based on stratified random sampling. Data collection was carried out using observations, interviews, and questionnaires. The hypotheses were tested using path analysis. The research results show that economic satisfaction, cooperative benefits, contributive benefits, and personal entrepreneurial quality are proven to have a significant effect on cooperative motivation. Meanwhile, the knowledge variable has no significant effect on cooperative motivation. The cooperative benefits have a significant effect on participation motivation, while the knowledge, contributive motivation, and personal entrepreneurial quality variables do not have a significant effect on participation motivation. Furthermore, economic satisfaction, cooperative motivation, and participation motivation do not have a significant effect on participation level. Finally, personal entrepreneurial quality and participation level do not have a significant effect on empowerment. Keywords: Model, empowerment, cooperatives, and micro, small, and medium enterprises